2018
DOI: 10.7717/peerj.4811
|View full text |Cite
|
Sign up to set email alerts
|

Endozoochory by mallard in New Zealand: what seeds are dispersed and how far?

Abstract: In Europe and North America waterfowl are major dispersers of aquatic and terrestrial plants, but in New Zealand their role has yet to be investigated. Mallards were introduced to New Zealand in the late 1800s, and today they are the most abundant and widespread waterfowl in the country. To assess seed dispersal, we radiomarked 284 female mallards from two study sites during the pre-breeding (June–August) and breeding (August–December) periods in 2014–2015, and examined movements that occurred within 24, 48 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 38 publications
(68 reference statements)
1
22
0
Order By: Relevance
“…(Farmer, Webb, Pierce, & Bradley, ; Kleyheeg et al, ; Reynolds & Cumming, ; Viana, Santamaría, Michot, & Figuerola, ). Waterbird endozoochory has now been demonstrated for a variety of terrestrial and aquatic plants that lack a fleshy fruit, although this does not coincide with the dispersal syndromes often assigned based on seed morphology (Bartel, Sheppard, Lovas‐Kiss, & Green, ; Lovas‐Kiss, Sanchez, et al, ; Lovas‐Kiss et al, ; Lovas‐Kiss, Vizi, et al, ). This is a form of “nonclassical endozoochory,” as it does not coincide with the “endozoochory syndrome” (Green, Elmberg, & Lovas‐Kiss, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Farmer, Webb, Pierce, & Bradley, ; Kleyheeg et al, ; Reynolds & Cumming, ; Viana, Santamaría, Michot, & Figuerola, ). Waterbird endozoochory has now been demonstrated for a variety of terrestrial and aquatic plants that lack a fleshy fruit, although this does not coincide with the dispersal syndromes often assigned based on seed morphology (Bartel, Sheppard, Lovas‐Kiss, & Green, ; Lovas‐Kiss, Sanchez, et al, ; Lovas‐Kiss et al, ; Lovas‐Kiss, Vizi, et al, ). This is a form of “nonclassical endozoochory,” as it does not coincide with the “endozoochory syndrome” (Green, Elmberg, & Lovas‐Kiss, ).…”
Section: Introductionmentioning
confidence: 99%
“…So far, our understanding of which plant species are dispersed by endozoochory by migratory waterbirds is limited by a general lack of empirical studies. However, those available show that plant species dispersed are associated with a range of terrestrial and wetland habitats and cannot be adequately predicted by simple classifications such as those commonly used to identify putative dispersal syndromes based on visual inspection of seed morphology(Bartel et al, 2018;Lovas-Kiss et al, 2019;Lovas-Kiss, Vizi, et al, 2018a;Soons et al, 2016). Indeed, this failure is inevitable since, by definition, no plants lacking a fleshy fruit can be assigned to the "endozoochory syndrome"(Pérez-Harguindeguy et al, 2013).…”
mentioning
confidence: 99%
“…To date, the majority of studies examining animal-mediated dispersal have focused on the transport of fleshy fruits in terrestrial systems (Figure 1; Czarnecka and Kitowski, 2013;Coughlan et al, 2017a;Bartel et al, 2018;Lovas-Kiss et al, 2018c). Despite this, evidence suggests that the assisted dispersal of whole organisms or propagule stages that lack a fleshy fruit, e.g., seeds, spores, eggs, ephippia, gemmules, statoblasts, or cysts, frequently occurs through either endozoochory (internal transport within the digestive system: Pellerin et al, 2016;Lovas-Kiss et al, 2018b,c) or ectozoochory (external adherence; synonyms epizoochorous, exozoochorous: Coughlan et al, 2017a;Lovas-Kiss et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…Although an array of valuable ecosystem services provided by dispersers have been repeatedly documented, the functional role of vector species, even possible keystone dispersers in mutualistic systems, remains poorly studied (Farwig and Berens, 2012;Mello et al, 2015). Moreover, research has revealed that vectors not traditionally associated with the dispersal of certain propagule taxa, frequently facilitate substantial dispersal events (Vanschoenwinkel et al, 2011;Farmer et al, 2017;Hämäläinen et al, 2017;Bartel et al, 2018). Dispersal events can be considered "primary dispersal" when organisms adhere to the external surfaces of vector species, or when dispersers feed directly on seeds, fruits, invertebrates or other propagule structures but fail to digest all of them (Coughlan et al, 2017b;Lovas-Kiss et al, 2018b,c).…”
Section: Introductionmentioning
confidence: 99%
“…For long-distance dispersal (LDD), Green and Figuerola (2005) in their thorough review of bird-mediated dispersal of zooplankton states that "... studies of LDD in aquatic systems remain in their infancy". Recent studies addressing the role of waterfowl and shorebirds for seed dispersal confirm a strong potential of endozoochory over short to moderate (< 20 km) distances (Bartel et al, 2018), but also long-distance dispersal across Europe (Lovas-Kiss et al, 2018). While it could be argued that plant seeds have a higher likelihood of being ingested and dispersed than aquatic animals, also resting stages of zooplankton may withstand gut passage.…”
Section: Introductionmentioning
confidence: 99%